Preparation method and application of catalyst for synthesizing deuterated ammonia

By etching molybdenum carbide through acid and alkaline treatment to form a layered structure and reacting with cobalt chloride hexahydrate, the Co/molybdenum carbide catalyst was prepared, which solved the problems of high cost of existing deuterated ammonia catalysts and harsh reaction conditions, and achieved effective catalyzing of the synthesis of deuterated ammonia under lower conditions, reducing production costs and safety risks.

CN119588388APending Publication Date: 2025-03-11PERIC SPECIAL GASES CO LTD

Patent Information

Application Number
CN202411714578.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing deuterated ammonia catalyst preparation methods are costly, and the reaction conditions are harsh and the pressure and temperature requirements are high.

Method used

Molybdenum carbide is used as the basic material, and a layered structure is formed through acid etching and alkaline treatment, and then reacted with cobalt chloride hexahydrate to form a Co/molybdenum carbide catalyst. This catalyst effectively catalyzes the synthesis of deuterated ammonia at lower pressures and temperatures.

Benefits of technology

It reduces the production cost of catalysts, reduces the pressure and temperature requirements of equipment, improves economic benefits, and reduces safety risks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a preparation method and application of a catalyst for synthesizing deuterated ammonia. The preparation method comprises the following steps: S1, adding molybdenum carbide into a hydrofluoric acid solution, magnetically stirring for 72-96 hours, washing and centrifuging with water, and repeatedly washing and centrifuging until the pH (Potential of Hydrogen) gt; 5, obtaining acid etching molybdenum carbide; s2, adding an alkaline solution into the acid-etched molybdenum carbide, carrying out ultrasonic treatment at room temperature until the pH value of the solution is 7, and then carrying out centrifugal solid-liquid separation to obtain layered molybdenum carbide; and S3, mixing the cobalt chloride hexahydrate solution and molybdenum carbide at 400-600 DEG C to react for 3-6 hours, and performing vacuum freeze drying to obtain the Co / molybdenum carbide catalyst. The catalyst prepared by the method is applied to synthesis of deuterated ammonia by reaction of nitrogen and deuterium gas, and is low in cost, pollution-free, high in conversion rate and simple to prepare.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of catalyst preparation, and specifically relates to a preparation method and application of a catalyst for synthesizing deuterated ammonia. Background Art

[0002] Deuterated ammonia, as a special chemical substance, is very important in the advanced manufacturing process of integrated circuits. Especially in the nano-processing lines of 14 nanometers and below, deuterated ammonia is widely used as a film-forming raw material. This application makes the film-forming process have higher quality, especially in terms of step coverage. Step coverage refers to the uniformity of the film covering the step structure at different heights in the integrated circuit. Good step coverage can ensure that the thickness of the film is consistent in all parts, thereby improving the performance and reliability of the overall circuit. As the semiconductor industry continues to move towards smaller process nodes, advanced processes of 14 nanometers and below have gradually become mainstream. It has not only promoted the technological progress of the entire industry, but also brought growth to the market demand for deuterated ammonia. With the continuous development and application of these advanced processes, the market potential of deuterated ammonia is also gradually increasing, becoming an indispensable part of the semiconductor manufacturing field. During use, deuterated ammonia can not only provide high-quality film-forming effects, but also produce deuterium, an isotope. Deuterium is a hydrogen isotope with a heavier molecular weight, and its application in semiconductor manufacturing has unique value. For example, deuterium can be used to make passivation layers for silicon nitride and silicon oxynitride. Passivation layers play a protective role in semiconductor devices, preventing the influence of the external environment on transistors, thereby extending the service life of transistors. Due to its heavy molecular weight, the use of deuterium in passivation layers can significantly increase the life of specific transistors, which is of great significance for improving the stability and reliability of integrated circuits.

[0003] At present, the industrialized preparation method of deuterated ammonia preferably uses nitrogen and deuterium gas synthesis routes. The traditional iron-based catalyst reaction conditions are harsh, with a pressure of 15-30 MPa and a temperature of more than 500°C. For example, the patent with the announcement number CN118874359A discloses a deuterated ammonia synthesis device, in which a catalytic bed is provided in a synthesis tower, and the catalyst filled in the catalyst bed is an iron-based catalyst or a ruthenium-based catalyst. The deuterium and nitrogen mixed gas is heated to 350-500°C by a heat exchanger from a raw gas tank and then introduced into the synthesis tower to synthesize deuterated ammonia. In recent years, research on ruthenium-based catalysts has also emerged in an endless stream, but the price is expensive. For example, the Chinese patented method for preparing deuterated ammonia and the deuteration reaction using it as a deuterium source, as disclosed in announcement number CN113526526A, specifically comprises the following steps: reacting a nitrile compound with a catalyst in a deuterium source atmosphere to obtain deuterated amine, wherein the catalyst is one or more of platinum, palladium, ruthenium, nickel, iridium, gold, silver, iron and copper. Summary of the invention

[0004] In view of the problems of high catalyst cost and high reaction temperature in the prior art for preparing deuterated ammonia, the present application proposes a preparation method and application of a catalyst for synthesizing deuterated ammonia.

[0005] The specific scheme of this application is:

[0006] On the one hand, the present application provides a method for preparing a catalyst for synthesizing deuterated ammonia, comprising the following steps:

[0007] Step S1. Add molybdenum carbide to a hydrofluoric acid solution, stir for 72 to 96 hours, wash with water and centrifuge, repeat the washing and centrifugation until the pH is greater than 5, and obtain acid-etched molybdenum carbide;

[0008] Step S2. adding an alkaline solution to the acid-etched molybdenum carbide, ultrasonically treating the solution at room temperature until the pH value of the solution is 7, and then centrifuging to separate the solid and liquid to obtain layered molybdenum carbide;

[0009] Step S3: mixing the cobalt chloride hexahydrate solution and molybdenum carbide at 400-600° C. for reaction for 3-6 hours, and freeze-drying in vacuum to obtain a Co / molybdenum carbide catalyst.

[0010] Preferably, the mass concentration of the hydrofluoric acid solution in step S1 is 10-90%, and the ratio of molybdenum carbide to the hydrofluoric acid solution is 1 g:20 mL.

[0011] Preferably, the stirring in step S1 is magnetic stirring, and the rotation speed is 3000-8000 r / min.

[0012] Preferably, the alkaline solution in step S2 is a potassium hydroxide solution or a sodium hydroxide solution, and the concentration of the alkaline solution is 0.2 mol / L.

[0013] Preferably, the ultrasonic treatment time in step S2 is 3 to 6 hours.

[0014] Preferably, the preparation method of the cobalt chloride hexahydrate solution in step S3 is: mixing cobalt chloride hexahydrate and deionized water in a ratio of 3g:10mL and stirring evenly.

[0015] Preferably, in step S3, the mass ratio of molybdenum carbide to cobalt chloride hexahydrate solution is 1:13, the temperature of vacuum freeze drying is -10 to -30°C, and the vacuum degree is 5 to 10 mTorr.

[0016] On the other hand, the present application provides an application of a method for preparing a catalyst for synthesizing deuterated ammonia, which is used to synthesize deuterated ammonia, specifically: nitrogen and deuterium gas are introduced into a reactor containing a Co / molybdenum carbide catalyst in a volume ratio of 1: (2.7 to 3.3) to generate deuterated ammonia.

[0017] Preferably, the reaction temperature is 300-500° C., the reaction pressure is 1-3 MPa, and the reaction time is 48-72 h.

[0018] The beneficial effects of this application are:

[0019] The present application is based on the strong acidity of hydrofluoric acid. Under the action of hydrofluoric acid, the carbon atoms in molybdenum carbide are gradually stripped out to form an oxide layer and fluoride ions. Finally, the residual acidic substances and auxiliary products are removed by washing to obtain the final layered molybdenum carbide material, and the layered molybdenum carbide material is immersed in a cobalt chloride hexahydrate solution. The cobalt chloride hexahydrate molecules are attached to the surface and pores of the layered molybdenum carbide by physical adsorption and chemical adsorption. Under high temperature conditions, the cobalt chloride hexahydrate undergoes decomposition and reduction reactions, and the chloride ions (Cl-) in the cobalt chloride molecules are removed and reduced to metal cobalt atoms. The reduced metal cobalt atoms react chemically with the layered molybdenum carbide to form a stable chemical bond. The metal cobalt atoms are gradually embedded in the lattice of molybdenum carbide to form a Co / molybdenum carbide catalyst. The catalyst prepared in the present application usually requires a higher pressure when preparing deuterated ammonia relative to iron-based catalysts, while the Co / molybdenum carbide catalyst achieves an effective catalytic reaction at 1 to 3 MPa, which helps to reduce equipment costs and safety risks. At the same time, the catalyst prepared in the present application has lower raw material cost than the ruthenium-based catalyst and the Co / molybdenum carbide catalyst, and cobalt and molybdenum carbide are common and cheap. Therefore, the use of the Co / molybdenum carbide catalyst of the present application can reduce production costs and improve economic benefits. DETAILED DESCRIPTION

[0020] In order to further explain the technical means and effects adopted by the present application to achieve the predetermined application purpose, a clear and complete description is given below in conjunction with the preferred embodiments.

[0021] Example 1

[0022] This embodiment provides a method for preparing a catalyst for synthesizing deuterated ammonia, which is as follows:

[0023] Step S1: Preparation of acid-etched molybdenum carbide

[0024] 50g of molybdenum carbide was selected as a raw material and added to 1000mL of hydrofluoric acid with a concentration of 50%. Subsequently, stirring was continued for 72 hours under magnetic stirring at 5000r / min to allow the molybdenum carbide to be fully etched by hydrofluoric acid. After the reaction was completed, the product was repeatedly washed and centrifuged with deionized water until the pH of the supernatant after centrifugation was 6, and the operation was stopped to obtain acid-etched molybdenum carbide.

[0025] Through the above operation, under the action of hydrofluoric acid, on the one hand, the impurity components in molybdenum carbide can be removed, and on the other hand, the carbon atoms in molybdenum carbide are gradually stripped out to form an oxide layer and fluoride ions. Finally, the residual acidic substances and auxiliary products are removed by washing to obtain the final layered molybdenum carbide material. The layered molybdenum carbide has a higher specific surface area and more active sites, which is conducive to the synthesis and stabilization of the subsequent catalyst.

[0026] Step S2: Alkaline solution neutralizes acid ions

[0027] 3L of 0.2 mol / L sodium hydroxide solution was added to the acid-etched molybdenum carbide obtained in step S1, and the solution was subjected to water bath ultrasonic treatment for 5 hours at room temperature until the pH value of the solution reached 7. Under the action of ultrasound, the OH in the alkaline solution - Ions enter the interlayers, neutralize the interlayers of layered molybdenum carbide and the H adsorbed on its surface + Finally, the solid-liquid separation is carried out by centrifugation to obtain molybdenum carbide with a layered structure.

[0028] Step S3: Impregnation Synthesis of Co / Molybdenum Carbide Catalyst

[0029] 30g of cobalt chloride hexahydrate and 100mL of deionized water were stirred at room temperature for 30min to obtain a cobalt chloride hexahydrate solution. Then, 10g of layered molybdenum carbide was mixed with the cobalt chloride hexahydrate solution and reacted at 500℃ for 5 hours. The cobalt chloride hexahydrate molecules were attached to the surface and pores of the layered molybdenum carbide by physical adsorption and chemical adsorption. Under high temperature conditions, the cobalt chloride hexahydrate decomposed and reduced, and the chloride ions (Cl-) in the cobalt chloride molecules were removed and reduced to metal cobalt atoms. The reduced metal cobalt atoms reacted chemically with the layered molybdenum carbide to form a stable chemical bond. The metal cobalt atoms were gradually embedded in the lattice of molybdenum carbide to form a Co / molybdenum carbide catalyst. After the reaction, the product was subjected to vacuum freeze-drying treatment. The temperature of the vacuum freeze-drying was controlled at -20℃ and the vacuum degree was maintained at 8mTorr to remove moisture and residual solvent in the product, and finally a pure Co / molybdenum carbide catalyst was obtained.

[0030] Example 2

[0031] This embodiment provides a method for preparing a catalyst for synthesizing deuterated ammonia, which is as follows:

[0032] Step S1: Preparation of acid-etched molybdenum carbide

[0033] 100g of molybdenum carbide was selected as a raw material and added to 2000mL of hydrofluoric acid with a concentration of 10%. Subsequently, the stirring was continued for 96 hours under magnetic stirring at 3000r / min to allow the molybdenum carbide to be fully etched by hydrofluoric acid. After the reaction was completed, the product was repeatedly washed and centrifuged with deionized water until the pH of the supernatant after centrifugation was 7, and the operation was stopped to obtain acid-etched molybdenum carbide.

[0034] Through the above operation, under the action of hydrofluoric acid, on the one hand, the impurity components in molybdenum carbide can be removed, and on the other hand, the carbon atoms in molybdenum carbide are gradually stripped out to form an oxide layer and fluoride ions. Finally, the residual acidic substances and auxiliary products are removed by washing to obtain the final layered molybdenum carbide material. The layered molybdenum carbide has a higher specific surface area and more active sites, which is conducive to the synthesis and stabilization of the subsequent catalyst.

[0035] Step S2: Alkaline solution neutralizes acid ions

[0036] 6L of 0.2mol / L potassium hydroxide solution was added to the acid-etched molybdenum carbide obtained in step S1, and the solution was subjected to water bath ultrasonic treatment for 3 hours at room temperature until the pH value of the solution reached 7. Under the action of ultrasound, the OH in the alkaline solution - Ions enter the interlayers, neutralize the interlayers of layered molybdenum carbide and the H adsorbed on its surface + Finally, the solid-liquid separation is carried out by centrifugation to obtain molybdenum carbide with a layered structure.

[0037] Step S3: Impregnation Synthesis of Co / Molybdenum Carbide Catalyst

[0038] 60g of cobalt chloride hexahydrate and 200mL of deionized water were stirred at room temperature for 30min to obtain a cobalt chloride hexahydrate solution. Then, 20g of layered molybdenum carbide was added to the cobalt chloride hexahydrate solution and reacted at 400°C for 6 hours. The cobalt chloride hexahydrate molecules were attached to the surface and pores of the layered molybdenum carbide by physical adsorption and chemical adsorption. Under high temperature conditions, the cobalt chloride hexahydrate decomposed and reduced, and the chloride ions (Cl-) in the cobalt chloride molecules were removed and reduced to metal cobalt atoms. The reduced metal cobalt atoms reacted chemically with the layered molybdenum carbide to form a stable chemical bond. The metal cobalt atoms were gradually embedded in the lattice of molybdenum carbide to form a Co / molybdenum carbide catalyst. After the reaction, the product was subjected to vacuum freeze drying. The temperature of the vacuum freeze drying was controlled at -10°C and the vacuum degree was maintained at 10mTorr to remove moisture and residual solvent in the product, and finally a pure Co / molybdenum carbide catalyst was obtained.

[0039] Example 3

[0040] This embodiment provides a method for preparing a catalyst for synthesizing deuterated ammonia, which is as follows:

[0041] Step S1: Preparation of acid-etched molybdenum carbide

[0042] 50g of molybdenum carbide was selected as a raw material and added to 1000mL of hydrofluoric acid with a concentration of 90%. Subsequently, stirring was continued for 90 hours under magnetic stirring at 8000r / min to allow the molybdenum carbide to be fully etched by hydrofluoric acid. After the reaction was completed, the product was repeatedly washed and centrifuged with deionized water until the pH of the supernatant after centrifugation was 5.5, and the operation was stopped to obtain acid-etched molybdenum carbide.

[0043] Through the above operation, under the action of hydrofluoric acid, on the one hand, the impurity components in molybdenum carbide can be removed, and on the other hand, the carbon atoms in molybdenum carbide are gradually stripped out to form an oxide layer and fluoride ions. Finally, the residual acidic substances and auxiliary products are removed by washing to obtain the final layered molybdenum carbide material. The layered molybdenum carbide has a higher specific surface area and more active sites, which is conducive to the synthesis and stabilization of the subsequent catalyst.

[0044] Step S2: Alkaline solution neutralizes acid ions

[0045] 3L of 0.2 mol / L sodium hydroxide solution was added to the acid-etched molybdenum carbide obtained in step S1, and the solution was subjected to water bath ultrasonic treatment for 6 hours at room temperature until the pH value of the solution reached 7. Under the action of ultrasound, the OH in the alkaline solution - Ions enter the interlayers, neutralize the interlayers of layered molybdenum carbide and the H adsorbed on its surface + Finally, the solid-liquid separation is carried out by centrifugation to obtain molybdenum carbide with a layered structure.

[0046] Step S3: Impregnation Synthesis of Co / Molybdenum Carbide Catalyst

[0047] 30g of cobalt chloride hexahydrate and 100mL of deionized water were stirred at room temperature for 30min to obtain a cobalt chloride hexahydrate solution. Then, 10g of layered molybdenum carbide was mixed with the cobalt chloride hexahydrate solution and reacted at 600℃ for 3 hours. The cobalt chloride hexahydrate molecules were attached to the surface and pores of the layered molybdenum carbide by physical adsorption and chemical adsorption. Under high temperature conditions, the cobalt chloride hexahydrate decomposed and reduced, and the chloride ions (Cl-) in the cobalt chloride molecules were removed and reduced to metal cobalt atoms. The reduced metal cobalt atoms reacted chemically with the layered molybdenum carbide to form a stable chemical bond. The metal cobalt atoms were gradually embedded in the lattice of molybdenum carbide to form a Co / molybdenum carbide catalyst. After the reaction, the product was subjected to vacuum freeze drying. The temperature of the vacuum freeze drying was controlled at -30℃ and the vacuum degree was maintained at 5mTorr to remove moisture and residual solvent in the product, and finally a pure Co / molybdenum carbide catalyst was obtained.

[0048] Application Examples 1 to 3 prepare deuterated ammonia based on the catalytic effect of the catalyst prepared in Examples 1 to 3.

[0049] Application Example 1

[0050] This application example provides an application of a catalyst for synthesizing deuterated ammonia, which is used to synthesize deuterated ammonia. Specifically, the catalyst prepared in Example 1 is first mechanically pressed into tablets and loaded into a reactor, and then the reactor is evacuated and replaced with nitrogen. Subsequently, nitrogen and deuterium gas are introduced into the reactor in a volume ratio of 1:3 to generate deuterated ammonia. The reaction temperature is 400°C, the reaction pressure is 3MPa, and the reaction time is 65h.

[0051] Application Example 2

[0052] This application example provides an application of a catalyst for synthesizing deuterated ammonia, which is used to synthesize deuterated ammonia, specifically: the catalyst prepared in Example 2 is first mechanically pressed into tablets and loaded into a reactor, and then the reactor is evacuated and replaced with nitrogen, and then nitrogen and deuterium gas are introduced into the reactor at a volume ratio of 1:2.7 and a flow rate of 300 mL / min to generate deuterated ammonia. The reaction temperature is 500°C, the reaction pressure is 1 MPa, and the reaction time is 72 h.

[0053] Application Example 3

[0054] This application example provides an application of a catalyst for synthesizing deuterated ammonia, which is used to synthesize deuterated ammonia, specifically: the catalyst prepared in Example 3 is first mechanically pressed into tablets and loaded into a reactor, and then the reactor is evacuated and replaced with nitrogen, and then nitrogen and deuterium gas are introduced into the reactor at a volume ratio of 1:3.3 and a flow rate of 300 mL / min to generate deuterated ammonia. The reaction temperature is 300°C, the reaction pressure is 23 MPa, and the reaction time is 48 h.

[0055] Based on the catalyst prepared in the present application, the generation amount and conversion rate of deuterated ammonia were measured, and the results are shown in Table 1.

[0056] Table 1

[0057] Application Examples Deuterated ammonia production / g Conversion rate / % Application Example 1 241.12 25.14 Application Example 2 258.30 26.92 Application Example 2 256.7 25.75

[0058] The above is only a preferred embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application has been disclosed as a preferred embodiment as above, it is not intended to limit the present application. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present application. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A method for preparing a catalyst for synthesizing deuterated ammonia, characterized in that: The steps include: Step S1. Add molybdenum carbide to a hydrofluoric acid solution, stir for 72 to 96 hours, wash with water and centrifuge, repeat the washing and centrifugation until the pH is greater than 5, and obtain acid-etched molybdenum carbide; Step S2. adding an alkaline solution to the acid-etched molybdenum carbide, ultrasonically treating the solution at room temperature until the pH value of the solution is 7, and then centrifuging to separate the solid and liquid to obtain layered molybdenum carbide; Step S3: mixing the cobalt chloride hexahydrate solution and molybdenum carbide at 400-600° C. for reaction for 3-6 hours, and freeze-drying in vacuum to obtain a Co / molybdenum carbide catalyst.

2. The method for preparing a catalyst for synthesizing deuterated ammonia according to claim 1, characterized in that: The mass concentration of the hydrofluoric acid solution in step S1 is 10-90%, and the ratio of molybdenum carbide to the hydrofluoric acid solution is 1 g:20 mL.

3. The method for preparing a catalyst for synthesizing deuterated ammonia according to claim 1, characterized in that: The stirring in step S1 is magnetic stirring, and the rotation speed is 3000-8000 r / min.

4. The method for preparing a catalyst for synthesizing deuterated ammonia according to claim 1, characterized in that: The alkaline solution in step S2 is a potassium hydroxide solution or a sodium hydroxide solution, and the concentration of the alkaline solution is 0.2 mol / L.

5. The method for preparing a catalyst for synthesizing deuterated ammonia according to claim 1, characterized in that: The ultrasonic treatment time in step S2 is 3 to 6 hours.

6. The method for preparing a catalyst for synthesizing deuterated ammonia according to claim 1, characterized in that: The preparation method of the cobalt chloride hexahydrate solution in step S3 is: cobalt chloride hexahydrate and deionized water are mixed and stirred in a ratio of 3 g:10 mL.

7. The method for preparing a catalyst for synthesizing deuterated ammonia according to claim 1, characterized in that: In step S3, the mass ratio of molybdenum carbide to cobalt chloride hexahydrate solution is 1:13, the temperature of vacuum freeze drying is -10 to -30°C, and the vacuum degree is 5 to 10 mTorr.

8. The use of the method for preparing a catalyst for synthesizing deuterated ammonia according to any one of claims 1 to 7, characterized in that: The method is used for synthesizing deuterated ammonia, specifically, nitrogen and deuterium are introduced into a reactor equipped with a Co / molybdenum carbide catalyst in a volume ratio of 1:(2.7-3.3) to generate deuterated ammonia.

9. Use of a catalyst for synthesizing deuterated ammonia according to claim 8, characterized in that: The reaction temperature is 300-500°C, the reaction pressure is 1-3MPa, and the reaction time is 48-72h.

Citation Information

Patent Citations

  • Preparation method of deuterated ammonia and deuteration reaction participated by deuterated ammonia as deuterium source

    CN113526526A

  • Deuterated ammonia synthesis device

    CN118874359A

Cited By

  • Deuterated ammonia synthesis catalyst as well as preparation method and application thereof

    CN120479421A